Presence of Dolosigranulum pigrum in the nasopharynx and its relationship with respiratory health status in paediatric population - Maria Cisneros; Desirée Henares; Aleix Lluansí; Pedro Brotons; Cristian Launes; Daniel Penela-Sanchez; Gerard Gonzalez-Comino; Amaresh Perez-Arguello; Mariona F. de Sevilla; Alex Mira; Miguel Blanco-Fuertes; Carmen Muñoz-Almagro (PLOS One, 2026)
Background Respiratory tract infections range from asymptomatic colonisation to an invasive disease. Recent studies suggest that nasopharyngeal microbiota may influence this variability. Emerging evidence points to Dolosigranulum pigrum, a nasopharyngeal commensal, as a potentially protective bacterium. This study aimed to identify variables associated with the presence of D. pigrum in the nasopharynx of children with varying respiratory health statuses. Methods Nasopharyngeal aspirates were collected from children 0.1% of total sequences obtained by 16S rRNA gene sequencing. Variables included sex, breastfeeding, delivery mode, S. pneumoniae carriage, respiratory viruses and clinical features. Results Among 140 children (73 males, 67 females), D. pigrum was detected in 79 (56.4%): 44/65 in the healthy group; 26/48 of viral and 9/27 IPD cases. Multivariate analysis revealed significant associations with health status and sex. Healthy children were more likely to carry D. pigrum than IPD cases (44/79 vs. 26/79; p = 0.028). Males were more frequently D. pigrum carriers than females (48/79 vs. 31/79; p = 0.033). Conclusion D. Pigrum was associated with respiratory health, being more prevalent in healthy children, and showed potential sex-related differences.